Comparison of current-source and voltage-source shunt active power filters for harmonic compensation and reactive power control - Pinto, J. G. (2012)
This paper presents the comparison between two three-phase Shunt Active Power Filters (SAPFs), one with Current-Source Inverter (CSI) and the other with Voltage-Source Inverter (VSI), which are used to compensate current harmonics and to control reactive power. The control algorithm of both SAPFs is based on the Instantaneous Reactive Power Theory (p-q Theory). The comparison here presented focuses on the Total Harmonic Distortion (THD) and RMS values of the compensated currents, and in the Total Power Factor (TPF) of the installation.